Double cantilever beam model for functionally graded materials based on two-dimensional theory of elasticity. (February 2015) - Chu, P.; Li, X.-F.; Wang, Z.-G.; Lee, K.Y.
Highlights: A double-cantilever beam of functionally graded materials is presented. Stress intensity factors are derived for an edge/centrally-cracked FGM layer. The influence of the gradient index on fracture parameters is discussed. Abstract: This paper extends the double cantilever beam (DCB) model to functionally graded materials (FGMs) based on two-dimensional theory of elasticity. A theoretical approach is proposed to determine strain energy release rate of a crack in a layered FGM with exponential gradient perpendicular to the crack plane. Elasticity solutions of a functionally graded cantilever subjected to a concentrated force and a bending moment are derived for thickness-wise varying Young's modulus. Using the derived elasticity solutions, the energy release rate and stress intensity factor for an edge crack and a central crack parallel to the surface are obtained. Numerical results are given to show the influence of gradient index on fracture parameters.